THE DISCOURSE AS A WAY OF FORMING THE SOCIAL REALITY - Додонова, В. І. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article is dedicated to the problem of alignment of discourse essence in linguistic and extralinguistic methodologies. The author analyses different approaches of modern Ukrainian and Western philosophers.